(Ne)strpno o spolu - Mikić, Jasna (Slovenščina 2.0, 2019)
With the participation of women in the public sphere and social relations, the need for a cultural transformation arose, which would represent and address both genders. One of the more important questions posed by many feminist linguists during the Second Wave Feminism was how the eradication of lin-guistic sexism could affect the situation of men and women in society. Many of the opponents of linguistic changes and imposing nonsexist alternatives did not agree with the premise of the interconnection of society and language, and pro-duced numerous arguments. The aim of the article is to present the typical ar-guments against linguistic changes that appeared in foreign (English-speaking) research in the 1970s, and find parallels with the recent arguments of Slovenian linguists. The aim of the article, as well as a long-term interest, is to better un-derstand the beliefs of the opponents of linguistic changes by identifying and knowing their arguments. We see this as a possible approach to a (potential) collaboration in the future
Keywords: androcentricity; androcentričnost; gender-sensitive language use; Jezik (jezikoslovje); Jezik in kultura; jezikovne spremembe; linguistic change; Seksizem; Spol (jezikoslovje); spolno občutljiva raba jezika; Spremembe